Áreas em que Python vem sendo utilizado no aprendizado de máquina: um mapeamento sistemático - Silva, Rafael Rodrigues da (2023)
Machine learning is a subfield of artificial intelligence that focuses on developing algorithms and models that allow computers to learn and make predictions about data. The combination of Python's simplicity, versatility, and support from the large community has made it a very popular choice for numerous tasks, such as evaluating large datasets with the help of machine learning algorithms. There is a growing interest in machine learning, its applications and implications, and its possible results, mainly with the use of the Python programming language. Despite this interest, no studies were found on the various areas of applications in which studies and investigations have been conducted. Thus, a systematic mapping was conducted in order to cooperate with an overview of areas and forms of applications. Initially, 274 studies on the use of Python in machine learning applicability were analyzed. Among these, only 25 studies met the inclusion and exclusion criteria for articles defined in this work. These 25 articles were selected and categorized according to their application area, Python libraries, algorithms and input data to be used. As a result, a map of research in the area was developed and the results of each article were identified, indicating that all 25 studies obtained positive results in their proposals.